Impacto de la normativa establecida por la agencia de regulación y control minero Arcom en las canteras de materiales de construcción de la mitad del mundo - Correa Correa, Jimmy Marcelo (2017)
The present of this academic article is to conduct research in the quarries of construction materials (arid and stony), located in the Middle of the world sector, corresponding ton Canton Quito; with respect to the economic, social and environmental impact caused by the application of the Regulation established by the Mining Regulation and Control Agency (ARCOM), which is a regulatory body belonging to the Ministry of Mining. To accomplish this purpose, a situational analysis was carried out of the concessionaires and people involved in the extraction of construction materials (arid, and stony), in relation to the impact of the current regulations, for which surveys were carried out, through the formulation of multiple choice questions, in order to identify positive and negative impacts of economic, social and environmental character.